Impacts of EPA Proposed Buffer–Zone Restrictions on Profitability of North Florida Potato Growers - John J. VanSickle; Scott Smith; Richard Weldon (EDIS, 2009)
FE794, a 4-page fact sheet by John J. VanSickle, Scott Smith, and Richard Weldon, reports the results of a study to characterize the impact of the proposed buffer-zone restriction on the economic returns to Florida potato-growers. Includes references. Published by the UF Department of Food and Resource Economics, March 2009.